Perianal Block for Open Hemorrhoidectomy: A Case Series - Muhammad Iqbal; Dewi Larasati Riono; Andi Husni Tanra; Yudi Gumara (Journal of Anesthesiology and Clinical Research, 2022)
Introduction: Hemorrhoidectomy is one of the most common anorectal surgeries performed in a surgical room or ambulatory clinic. The procedure is linked to severe postoperative pain. Both general and regional anesthesia with spinal anesthesia is used in anorectal surgery. However, these predominantly used anesthesia methods leave postoperative side effects of nausea, vomitus, urinary retention, headache, dizziness, back pain, prolonged inferior muscle weakness, and the level of postoperative pain after the anesthesia wears off. Case presentation: Three cases of severe hemorrhoids were reported, and they underwent open hemorrhoidectomy with a perianal block. Postoperatively, all cases reported no side effects, minimal level of pain, and faster recovery. Recently, the perianal block has been used to curtail the side effects. Conclusion: Perianal block is performed by infiltrating the inferior rectal nerves innervating the anus and sphincter muscle. Sedation is sometimes performed prior to injection of the anesthetic block. This technique is considered safe and effective for hemorrhoidectomy.